2017
DOI: 10.1155/2017/3493687
|View full text |Cite
|
Sign up to set email alerts
|

Joint Optimization of Preventive Maintenance and Spare Parts Inventory with Appointment Policy

Abstract: Under the background of the wide application of condition-based maintenance (CBM) in maintenance practice, the joint optimization of maintenance and spare parts inventory is becoming a hot research to take full advantage of CBM and reduce the operational cost. In order to avoid both the high inventory level and the shortage of spare parts, an appointment policy of spare parts is first proposed based on the prediction of remaining useful lifetime, and then a corresponding joint optimization model of preventive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…Although, showed that the ( s, S ) inventory is not optimal even when cooperating with the optimal replacement decision. Cai, Yin, Zhang, and Chen (2017) proposed an appointment policy which reserves a spare to a specific unit when the deterioration reaches a particular threshold. In their method, the inventory level would be larger than the determined level under some conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, showed that the ( s, S ) inventory is not optimal even when cooperating with the optimal replacement decision. Cai, Yin, Zhang, and Chen (2017) proposed an appointment policy which reserves a spare to a specific unit when the deterioration reaches a particular threshold. In their method, the inventory level would be larger than the determined level under some conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The MDP model, first developed by Bellman (1957) , is first proposed as an approach because it is useful for a broad range of problems where the payoff is partly based on a dynamic environment and partly based on decision maker's behaviors. The essential elements of an MDP model are the states, actions, transition probability, and the reward function, all of which are explained in detail below.…”
Section: Markov Decision Process Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Many research of joint optimization of spare parts inventory and maintenance also presented not only in literature but also models have been proposed. Research proposed by [4] discusses about joint optimization of inventory and maintenance for critical and non critical spare part in multi echelon inventory. Another research proposed by (Sheng , 2016) that discussed about joint optimization of spare parts inventory and maintenance in the aviation field.…”
Section: Related Studymentioning
confidence: 99%
“…Finally, turning to solution methodology, the use of simulation to analyse joint policies is common for realistic settings [33,37,[44][45][46]. Simulation has the flexibility to address the increasingly complex and dynamic nature of maintenance optimisation, and inventory optimisation adds to this complexity.…”
Section: Introductionmentioning
confidence: 99%